Religiosity as a potential mediator for violence in childhood and adulthood: results from a Brazilian nationally representative survey - Homero Vallada; Ronaldo Laranjeira; Juliane Piasseschi de Bernardin Gonçalves; Giancarlo Lucchetti; Maria do Rosario Dias Latorre (BMJ Open)
Objectives Although previous studies have investigated the role of religiosity in violence outcomes, there is a lack of studies including this aspect as a mediator for violence in childhood and adulthood. This study aimed to investigate the relationship between religiosity and violence in childhood, as well as the possible mediating role of religiosity between suffering violence in childhood and suffering and/or perpetrating violence in adulthood.Design Cross-sectional population-based study carried out from November 2011 to March 2012.Setting Face-to-face surveys (at participants’ homes) were performed in a Brazilian nationally representative sample.Participants A total of 3378 adults (aged 19 years and above) were included.Primary and secondary outcomes measures The association between suffering violence in childhood and religiosity, and the mediating role of religiosity between childhood and adulthood violence were analysed using logistic regression models.Results Religiosity was associated with childhood violence, showing that those who suffered less violence in childhood were more religious in adulthood and considered religion more important in their lives. However, while there was a significant association between suffering violence during childhood and suffering and/or perpetrating violence in adulthood, religiosity did not mediate this relationship.Conclusions Although religious individuals self-reported less violence suffered in childhood, religiosity did not show evidence of being a potential mediator for childhood and adulthood violence (experienced and/or perpetrated). These results could help researchers explore this phenomenon, and aid health professionals and managers when proposing future interventions.